Photosynthetic Antenna‐Reaction Center Mimicry with a Covalently Linked Monostyryl Boron‐Dipyrromethene–Aza‐Boron‐Dipyrromethene–C60 Triad. Issue 34 (10th July 2013) - Shi, Wen‐Jing; El‐Khouly, Mohamed E.; Ohkubo, Kei; Fukuzumi, Shunichi; Ng, Dennis K. P.
Abstract An efficient functional mimic of the photosynthetic antenna‐reaction center has been designed and synthesized. The model contains a near‐infrared‐absorbing aza‐boron‐dipyrromethene (ADP) that is connected to a monostyryl boron‐dipyrromethene (BDP) by a click reaction and to a fullerene (C60) using the Prato reaction. The intramolecular photoinduced energy and electron‐transfer processes of this triad as well as the corresponding dyads BDP‐ADP and ADP‐C60 have been studied with steady‐state and time‐resolved absorption and fluorescence spectroscopic methods in benzonitrile. Upon excitation, the BDP moiety of the triad is significantly quenched due to energy transfer to the ADP core, which subsequently transfers an electron to the fullerene unit. Cyclic and differential pulse voltammetric studies have revealed the redox states of the components, which allow estimation of the energies of the charge‐separated states. Such calculations show that electron transfer from the singlet excited ADP (1ADP*) to C60 yielding ADP.+‐C60.− is energetically favorable. By using femtosecond laser flash photolysis, concrete evidence has been obtained for the occurrence of energy transfer from 1BDP* to ADP in the dyad BDP‐ADP and electron transfer from 1ADP* to C60 in the dyad ADP‐C60. Sequential energy and electron transfer have also been clearly observed in the triad BDP‐ADP‐C60. By monitoring the rise of ADP emission, it has been found that the rate of energy transfer is fast (≈1011 s−1). The dynamics of electron transfer through 1ADP* has also been studied by monitoring the formation of C60 radical anion at 1000 nm. A fast charge‐separation process from 1ADP* to C60 has been detected, which gives the relatively long‐lived BDP‐ADP.+C60.− with a lifetime of 1.47 ns. As shown by nanosecond transient absorption measurements, the charge‐separated state decays slowly to populate mainly the triplet state of ADP before returning to the ground state. These findings show that the dyads BDP‐ADP and ADP‐C60, and the triad BDP‐ADP‐C60 are interesting artificial analogues that can mimic the antenna and reaction center of the natural photosynthetic systems.